More than health care: The implications of cultural diversity for health care practice in Norway (Journal of Comparative Social Work, 2022)
The Norwegian community health centres are one of the main providers of maternal and child health care services. They are often the primary, as well as a regular point of contact, for women during pregnancy and after childbirth. As such, they are a place where encounters between primary health care providers like public health nurses, midwives and immigrant women, are frequent.Midwives and public health nurses play an important role as state employees in the distribution of universal health provisions at the local level. This is especially important in meeting the diverse needs of service users in a universal health care system. This study investigates the implications of cultural diversity for health care practice in a universal system. It employs a qualitative approach, using data from nine semi-structured interviews with midwives and public health nurses across three Norwegian municipalities. It analyses their experiences in working with immigrant women during pregnancy, and after childbirth, through thematic analysis. The findings illustrate the practitioners’ different approaches to meeting with culturally diverse patients, the challenges they face in their work, and how they overcome them. The discussions address the practice of cross-cultural health care in the absence of national guidelines or formal training using street-level bureaucracy as an analytical concept. This article contributes to knowledge on the practice of cross-cultural health care at Norwegian community health centres in the absence of a culturally cognizant health policy. On a broader scale, this study illustrates the implications of diversity for policy and practice in a universal welfare state.